Obesity, central adiposity and cardiometabolic risk factors in children and adolescents: a family‐based study. Issue 3 (27th March 2014) - Ali, O.; Cerjak, D.; Kent, J. W.; James, R.; Blangero, J.; Zhang, Y.
Summary Objective The objective of this study was to assess genetic and phenotypic correlations of obesity‐related cardiometabolic risk factors in a family‐based cohort. Methods Anthropometric, body composition and biochemical measurements were collected on 999 members of 111 extended Midwestern US families of Northern European origin. Forward stepwise regression was used to identify which of Tanner stage, sex, Tanner stage by sex, body fat mass index, body fat percentage (dual‐energy X‐ray absorptiometry), visceral fat (VF)/subcutaneous fat (SubQF) (computed tomography scans for adults or magnetic resonance imaging for children), VF, SubQF, body mass index (BMI)% and waist to height ratio most influence homeostasis model assessment (HOMA), high‐density lipoprotein cholesterol (HDL‐c), plasma triglycerides (TG) and low‐density lipoprotein cholesterol (LDL‐c). Results In children and adolescents, subcutaneous adiposity was the most significant covariate for HOMA (P < 0.001) and TG (P = 0.001), and BMI percentile for HDL‐c (P = 0.002) and LDL‐c (P < 0.001). In adults, waist–height ratio (P < 0.001), VF/SubQF ratio (P = 0.001) and BMI (P = 0.02) were most significant for HOMA; VF (P < 0.001) and BMI (P = 0.02) for TG and VF for LDL‐c (P = 0.001). Conclusion Subcutaneous adiposity at the waist is a more significant predictor of metabolic syndrome traits in children and adolescents than it is in adults.